Avaliação da potencial atividade citotóxica da peçonha de Caudisona Durissa Collilineata em células mononucleares do sangue periférico humano - Maineri, Marilissa Maciel (2012)
Venomous snakes have a real cocktail of pharmacological active substances and drugs that act powerfully against microorganisms. The objective of the present study was to evaluate in vitro the potential cytotoxic activity of Caudisona durissa collilineata venom in mononuclear cells (MNC) of peripheral human blood. After obtaining MNC for cell culture, the cytotoxic effect of different concentrations of crude venom was evaluated. The peripheral blood MNC were separated using a density gradient and were incubated (2x105 cells/well) with different venom concentrations (50, 5, 0,5, 0,05, 0,005 e 0,0005 µg/mL) for different times (1, 3, 6, 24, 48 e 72h) and in different substrates (PHA, IL visually examining the plates after 24, 48 and 72 hours. Was also observed with different concentrations of crude venom induced ADN fragmentation in MNC. We observed that the toxicity of crude C. d. collilineata venom varies proportionally with concentration, i.e., the higher the concentration, the higher its cytotoxicity. For this reason the 0.0005µg/mL concentration of crude Caudisona durissa collilineata venom presented the lowest cytotoxic activity in peripheral human blood MNC and that the fragmentation of cellular ADN was not seen in this study. Thus, it is suggested to employ two or more different assays to confirm the induction of cell death is occurring through apoptosis.